2012
DOI: 10.1016/j.spinee.2012.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblasts exhibit a more differentiated phenotype and increased bone morphogenetic protein production on titanium alloy substrates than on poly-ether-ether-ketone

Abstract: Background Context Multiple biomaterials are clinically available to spine surgeons for performing interbody fusion. Poly-ether-ether-ketone (PEEK) is used frequently for lumbar spine interbody fusion, but alternative materials are also used, including titanium (Ti) alloys. Previously, we showed that osteoblasts exhibit a more differentiated phenotype when grown on machined or grit-blasted titanium aluminum vanadium (Ti6Al4V) alloys with micron-scale roughened surfaces than when grown on smoother Ti6Al4V surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
130
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 185 publications
(144 citation statements)
references
References 52 publications
14
130
0
Order By: Relevance
“…Other authors have supported these observations as they relate to PEEK and Ti. 67,68 The anti-infectivity of Si 3 N 4 may also relate to surface chemistry, and the authors' observations are consistent with previous data with polymeric coatings containing chitosan, a material similar to Si 3 N 4 in terms of a net positive charge and the presence of amine groups at the surface. [52][53][54][55][56] The interaction of these groups with negatively charged bacteria reportedly leads to membrane disruption and lysis in chitosan-containing polymers.…”
supporting
confidence: 89%
“…Other authors have supported these observations as they relate to PEEK and Ti. 67,68 The anti-infectivity of Si 3 N 4 may also relate to surface chemistry, and the authors' observations are consistent with previous data with polymeric coatings containing chitosan, a material similar to Si 3 N 4 in terms of a net positive charge and the presence of amine groups at the surface. [52][53][54][55][56] The interaction of these groups with negatively charged bacteria reportedly leads to membrane disruption and lysis in chitosan-containing polymers.…”
supporting
confidence: 89%
“…34 Previous work has found that an implant's surface topology and roughness can be strategically tailored to optimize and accelerate in vitro cellularmaterial interactions. 35,36 Inspiration for such work stems from investigating natural bone turnover and healing, where osteoclasts prepare the surface to be remodeled with micron-scale roughness that aids in initiating subsequent osteoblastic activity. 37 Therefore, spinal implant surfaces modified to have micron-scale roughness may similarly stimulate osteoblasts to form bone matrix on the surface.…”
Section: Discussionmentioning
confidence: 99%
“…Rapuano et al [28] reported that Ti-alloy can form a superficial oxide layer which promoted osteoblast attachment through binding of adsorbed fibronectin to surface-expressed osteoblast integrins. Moreover, Olivares-Navarrete et al [29] found that culture of MG 63 osteoblast-like cells on Ti6Al-4V can promote osteogenic maturation and create an osteogenic environment that could enhance bone formation and implant stability. Mechanical property of the implant is another factor which affects osseointegration.…”
Section: Osseointegration and Bone In-growthmentioning
confidence: 99%